Evaluation of ForenSeq™ Signature Prep Kit B on predicting eye and hair coloration as well as biogeographical ancestry by using Universal Analysis Software (UAS) and available web‐tools. Issue 9 (15th February 2019) - Sharma, Vishakha; Jani, Krupa; Khosla, Pavan; Butler, Erin; Siegel, Donald; Wurmbach, Elisa
Abstract: This study examined 266 individuals from various populations including African American, East Asian, South Asian, European, and mixed populations to evaluate the ForenSeq™ Signature Prep Kit Primer Mix B. Focus was placed on phenotypic and biogeographical ancestry predictions by Illumina's Universal Analysis Software (UAS). These outcomes were compared to those obtained through web‐tools developed at the Erasmus Medical Center (EMC) and available from the Forensic Resource/Reference on Genetics‐knowledge base (FROG‐kb), as well as to eye color predictions by the 8‐plex system. Due to drop‐outs, predictions for eye and hair color by UAS failed for various samples in each run. By including reads below thresholds, predictions could be obtained for all samples through the web‐tools. Eye and hair color predictions for African Americans, East Asians, and South Asians showed no errors. Difficulties however, were noted in intermediate (neither blue nor brown) eye color predictions. These were mitigated by the 8‐plex system through exclusion of one eye color (e.g. "not brown"). Additionally, notable discrepancies were observed in hair color predictions, where some black/dark‐brown haired individuals were predicted to have blond hair. Overall, ancestry predictions were more accurate by FROG‐kb compared to UAS, which did not predict South Asian ancestry, particularly Indian individuals.